2019
DOI: 10.1177/0361198119837194
|View full text |Cite
|
Sign up to set email alerts
|

Use of Aerial LiDAR in Measuring Streetscape and Street Trees

Abstract: This paper investigates the usefulness of 3D volumetric pixels (voxels) and the United States Geological Survey (USGS) Quality Level 2 (QL2) Light Detection and Ranging (LiDAR) data to measure features in streetscapes. As the USGS embarks on a national LiDAR database with the goal of covering the entire United States of America (U.S.) with QL2 data or better, this paper investigates uses of QL2 LiDAR for the 3D measuring of streetscapes. Tree mapping is a common use of QL2 LiDAR data, and street trees are amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…As mentioned in the introduction, there are conflicting research findings about the impact street trees and landscape improvements have on road safety, and one possible source of conflict has been our inability to measure these features properly. The authors' previous study exploring the limits of USGS QL2 data expresses and legitimizes voxel use for measuring trees (5). Though some manual classification is involved with the QL1 process, actual objective and measurable landscape features can coincide with street tree data to assist with such research.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned in the introduction, there are conflicting research findings about the impact street trees and landscape improvements have on road safety, and one possible source of conflict has been our inability to measure these features properly. The authors' previous study exploring the limits of USGS QL2 data expresses and legitimizes voxel use for measuring trees (5). Though some manual classification is involved with the QL1 process, actual objective and measurable landscape features can coincide with street tree data to assist with such research.…”
Section: Resultsmentioning
confidence: 99%
“…Golombek and Marshall (5) explored the limits of QL2 data by designating streetscapes in three-dimensional (3D) pixels-better known as ''voxel'' grids-and found that QL2 data for measuring streetscapes is primarily limited to buildings and street trees. Since understanding the impacts of street trees and other clear zone objects is an important transportation topic, that study also discussed how 3D measurement of street trees widely differs from traditional 2D-derived canopy data.…”
mentioning
confidence: 99%
“…Mobile LiDAR has potential to fill these gaps. In addition to our previous studies (Golombek and Marshall 2019 , 2020 ), examples above from Lehtomaki et al, Wu et al, Gargoum et al, and Yang et al all utilized voxel-based approaches to advance their stated methods for measuring and quantifying urban features. Automated classification methods are quickly evolving for large-scale/area classification but are currently questionable regarding their exactness.…”
Section: Introductionmentioning
confidence: 99%
“…Research by Golombek and Marshall, for instance, explored the streetscape mapping and streetscape feature detection/extraction capabilities of publicly available aerial LiDAR data. More specifically, this research tested data derived from the national United States Geological Survey (USGS) 3D elevation program, which included Quality Level (QL) 2 LiDAR data (Golombek and Marshall 2019 ) as well as the four times denser QL1 LiDAR data (Golombek and Marshall 2020 ). QL2 LiDAR has a point density of at least 2 points per square meter while QL1 LiDAR is at least 8 points per square meter.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation